α-Coupled Fixed Points and Their Application in Dynamic Programming - J. Harjani; J. Rocha; K. Sadarangani (Abstract and Applied Analysis)
We introduce the definition of α-coupled fixed point in the space of the bounded functions on a set S and we present a result about the existence and uniqueness of such points. Moreover, as an application of our result, we study the problem of existence and uniqueness of solutions for a class of systems of functional equations arising in dynamic programming.